(untitled) (Journal of Atomic and Molecular Sciences, 2014)
A molecular beam experiment on the formation of H^+_3 has been carried out by using tunable vacuum ultraviolet (VUV) synchrotron radiation. Reflectron time-of-flight mass spectrometer is applied to detect the signal of H^+_3. The ionization energy (IE) of H_2 and the appearance energy (AE) of H^+_3 are determined to be 15.41 eV and 14.61 eV, respectively, by measurements of photoionization efficiency (PIE) curves. Additionally, two most likely H^+_3 formation ways, (H_2)2→ H^3_+ +H and (H_2)_3 → H^+_3 +H+H_2, are discussed by ab initio calculations at CCSD(T) and MP2 level with aug-cc-pVQZ basis set and compared with the experimental result. The optimized geometries of species involved in the dissociative photoionization channels are also determined at MP2/aug-cc-pVQZ level.